Legal Policy on the Conversion of Agricultural Land Functions in Ngawi Regency - Hari Soeseno Hardjoloekito; Meiyana Hikmawati; Heru Drajat Sulistyo (PT FORMOSA CENDEKIA GLOBAL, 2022)
Increased land use change is correlated with population growth in a given location. The process of changing the use of agricultural land from agriculture to other uses on some or all of the land area is known as conversion of agricultural land, and it typically has a negative influence on the environment and the potential of the land. The government needs to address the major issue of the change of agricultural land uses, particularly paddy fields to non-agricultural areas. The aim of this study is to ascertain the extent of land conversion in Ngawi Regency and the relationship between the phenomena of land conversion and the use of local laws there.An method known as descriptive qualitative is used in this investigation. Through the finding and narrative presentation of data, we shall interpret phenomena in this study. A conclusion that can be drawn from the research is that agricultural land in Ngawi Regency deteriorates year after year. This results from the development of communities, toll highways, and industrial areas on formerly agricultural territory. In Ngawi Regency, the execution of law enforcement in relation to land use changes has not been done adequately